Relationship between neutrophil-to-lymphocyte ratio and pulmonary arterial hypertension in non-dialytic patients with chronic kidney disease stage 5 - 冯世尧; 任伟 (Linchuang shenzangbing zazhi)
Objective To investigate the clinical value of neutrophil-to-lymphocyte ratio(NLR)for pulmonary arterial hypertension(PAH)in non-dialytic patients with chronic kidney disease(CKD) stage 5.Methods A total of 144 non-dialysis patients with CKD stage 5 were divided into two groups:PAH group and non-PAH group according to pulmonary artery systolic pressure.Clinical data were compared between the two groups,Spearman correlation analysis was used to analyze the relationship between pulmonary artery systolic pressure and various factors.Binary classification Logistic regression analysis was applied to analyze the risk factors of PAH.Receiver operating characteristic(ROC)curve was adopted to evaluate the predictive value of NLR for PAH.Results There were 64 cases(44.4%)in the PAH group and 80 cases(55.6%)in the non-PAH group.NLR,platelet to lymphocyte ratio,left internal atrial diameter and main pulmonary internal artery diameter in the PAH group were significantly higher than those in the non-PAH group(P<0.05).Lymphocyte count,hemoglobin,serum iron,triglyceride,very low density lipoprotein cholesterol and left ventricular ejection fraction in the PAH group were significantly lower than those in the non-PAH group,with all statistically significant differences(P<0.05).NLR,left atrial diameter and main pulmonary artery diameter were positively correlated with pulmonary artery systolic pressure(P<0.05).Multivariate Logistic analysis showed that,NLR(OR=2.151,95%CI 1.438～3.218,P<0.001),left atrial diameter(OR=1.176,95%CI 1.068～1.294,P<0.05)and main pulmonary artery diameter(OR=1.229,95%CI 1.004～1.504,P<0.05)were independent risk factors for PAH.The results of ROC curve analysis showed that the area under curve of PAH predicted from NLR was 0.711(95% CI 0.626～0.797,P<0.05).When the NLR cutoff value was 3.23,the sensitivity and specificity for predicting the occurrence of PAH in non-dialysis patients with CKD stage 5 were 60.9% and 72.5%,respectively.Conclusions NLR has a good clinical value in predicting the occurrence of PAH in non-dialysis patients with CKD stage 5.Left atrial enlargement and main pulmonary artery enlargement were related to PAH.